Momentum and market correlation - Badshah, I; Kolari, JW; Liu, W; Shin, S (New Zealand Finance Colloquium, 2016)
This paper proposes that an important source of momentum profits is market information associated with correlation to general market movements. Empirical tests for U.S. stocks in the sample period 1965 to 2013 indicate that most momentum profits can be attributed to the correlation of big- and medium-capitalization stocks with the CRSP market index. Further results show that small loser stocks have low correlation to the market and post-formation return reversal, small losers can be added to long winner portfolios to enhance profits, and momentum crashes can be reduced by suspending portfolio formation in bear markets. We conclude that momentum profits are related to market information and therefore not entirely anomalous as commonly believed.